Margaret Chase Smith: Woman of Courage - Graham, Frank Jr. (John Day Company New York, 1964)
This book is an informal biography of Margaret Chase Smith, Senator from Maine and the first woman in a major political party to announce her candidacy for Presidency of the United States.
Keywords: Smith, Margaret Chase -- 1897-1995; Senator -- Maine